Need For Career Guidance in the Almajiri School System in Nigeria: Implication for in-School Adolescents - Bolu-Steve, Foluke Nike; Okesina, Falilat Anike (Jurnal Kajian Bimbingan dan Konseling, 2023)
The study investigated the need for career guidance in the Almajiri school system as perceived by teachers in Kebbi State, Nigeria. The population consisted of all teachers within the state. The researchers purposively selected six large schools in Brinin Kebbi which is the state capital, and another six large secondary schools in Argungu. Fifty teachers were picked in each of the schools using simple random sampling technique. Thus, a total of six hundred respondents partook in this study. Need for Career Guidance in Almajiri schools (NCGASQ) was the instrument used in this study. The questionnaire was the major instrument used to gather data from the respondents. This instrument was divided into two sections. Section A contains respondents’ demographic data, similarly, Section B comprises information that elicits responses on the need for career guidance among the Amanjiri in Kebbi State. The findings showed that the perception of the respondents based on gender and educational level were the same. However, respondents’ career perceptions differed according to age and religion. The information given by respondents between the age group of 42 years and above differed significantly from those of the other groups, while the differences were noted in the responses of those practicing African traditional religion. It was however recommended that the government should employ trained career counsellors in the Almanjiri school system this will equally assist these students.